2014
DOI: 10.1038/ncomms5911
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sensing with switchable transport channels in graphene grain boundaries

Abstract: Grain boundaries can markedly affect the electronic, thermal, mechanical and optical properties of a polycrystalline graphene. While in many applications the presence of grain boundaries in graphene is undesired, here we show that they have an ideal structure for the detection of chemical analytes. We observe that an isolated graphene grain boundary has B300 times higher sensitivity to the adsorbed gas molecules than a single-crystalline graphene grain. Our electronic structure and transport modelling reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(133 citation statements)
references
References 35 publications
6
127
0
Order By: Relevance
“…GB [18][19][20][21][23][24][25][26][27]. The origin of this enhanced resistance has been probed with scanning tunneling spectroscopy (STS), and these measurements have revealed that GBs tend to be n-doped compared to the surrounding grains, such that they act as an electrical potential barrier to charge transport [40,41].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
See 1 more Smart Citation
“…GB [18][19][20][21][23][24][25][26][27]. The origin of this enhanced resistance has been probed with scanning tunneling spectroscopy (STS), and these measurements have revealed that GBs tend to be n-doped compared to the surrounding grains, such that they act as an electrical potential barrier to charge transport [40,41].…”
Section: Electrical Resistivity Of Individual Gbsmentioning
confidence: 99%
“…Therefore, because of its promise for large-area electronic applications, a detailed understanding of the electrical transport properties of polycrystalline graphene is crucial. To this end, a great deal of experimental [13,[18][19][20][21][22][23][24][25][26][27] and theoretical [7,[28][29][30][31][32][33][34][35][36][37][38] effort has has been devoted to studying charge transport across individual graphene GBs, and several reviews have already discussed this topic in great detail [5,26,39]. Therefore, here we briefly summarize the main features of electrical transport across individual graphene GBs before shifting our focus to a more global perspective of charge transport in polycrystalline graphene.…”
Section: Charge Transport In Polycrystalline Graphenementioning
confidence: 99%
“…There is also strong scientific interest in graphene GBs due to their onedimensional nature. Some examples include a bimodal phonon scattering behaviour across graphene GBs 7 , anomalous strength characteristics 3,8 , strong chemical sensitivity of boundary charge transform 9 , a transformation of the GBs from transparency of charge carriers to near-perfect reflection 10 , amongst others. A large number of theoretical studies on graphene GB structures have been performed by many researchers .…”
Section: Introductionmentioning
confidence: 99%
“…In polycrystalline graphene, the grain boundaries (GBs) between misoriented grains consist of a series of non-hexagonal rings [16][17][18] that can impede charge transport through the material [19][20][21] . In addition, GBs tend to be more chemically reactive than pristine graphene, which can also strongly impact charge transport, making this material interesting for gas sensing applications 22,23 . Prior studies have examined the impact of hydrogenation on the electronic transport properties of polycrystalline graphene 9,24 , but the detailed nature of the interaction between GBs and hydrogen adsorbates remains unclear.…”
Section: Since Its Experimental Isolation In 2004mentioning
confidence: 99%